THE ROLE OF PROFESSIONAL ETHICS COURSES ON THE DEVELOPMENT OF ETHICAL BEHAVIOR AND SOFT SKILLS FOR STUDENTS, TANGERANG CITY - Theodora, Paula (Institut Pendidikan Indonesia, 2025)
This research aims to analyze the learning of professional ethics. Professional ethics is very important for students to shape their character, improve their work readiness, build a positive reputation, and develop professional networks. By understanding and applying ethics from an early age, students will not only succeed in their studies but will also be prepared to face challenges in the professional world responsibly and with integrity. Data was collected thru Google Forms and analysis of course syllabi from various study programs at the university. The research method uses a quantitative approach with a survey of 190 students from D3, S1 Management, and S1 Accounting departments who have taken the Professional Ethics course. The research results show a significant positive correlation between understanding the material of Professional Ethics and the improvement of students' ethical behavior and soft skills.This research provides recommendations for improving the effectiveness of the professional ethics course, including the use of case-based learning methods, the integration of technology in ethics teaching, and closer collaboration with industry practitioners.